2018
DOI: 10.56093/ijans.v88i7.81408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GandhPaalashi (Hedychium spicatum) on the expression of hepatic genes associated with biotransformation, antioxidant and immune systems in WLH cockerels fed indoxacarb

Abstract: The objective of the present study was to evaluate the efficacy of Hedychium spicatum (HSRP) root powder, to ameliorate changes in gene expression in WLH cockerels fed indoxacarb. After 16 weeks of treatment, all birds from different groups were sacrificed humanly and collected the liver pieces in RNA later for expression study by RT-PCR to evaluate changes in the expression of genes involved in antioxidant function [catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione S-transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The protective effect of Hedychium spicatum rhizome powder with concentrations of 4000 ppm and 2000 ppm was tested against 250 ppm IC 50 of Indoxacarb-induced toxicity on a group of cockerels. The ameliorative effect of Hedychium spicatum root powder and its ability to restore the gene activities and expression of antioxidant, biotransformation, and immune system genes were demonstrated in cockerels fed Indoxacarb [ 77 , 93 , 94 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effect of Hedychium spicatum rhizome powder with concentrations of 4000 ppm and 2000 ppm was tested against 250 ppm IC 50 of Indoxacarb-induced toxicity on a group of cockerels. The ameliorative effect of Hedychium spicatum root powder and its ability to restore the gene activities and expression of antioxidant, biotransformation, and immune system genes were demonstrated in cockerels fed Indoxacarb [ 77 , 93 , 94 ].…”
Section: Methodsmentioning
confidence: 99%
“…The protective effect of Hedychium spicatum rhizome powder with concentrations of 4000 ppm and 2000 ppm was tested against 250 ppm IC 50 of Indoxacarb-induced toxicity on a group of cockerels. The ameliorative effect of Hedychium spicatum root powder and its ability to restore the gene activities and expression of antioxidant, biotransformation, and immune system genes were demonstrated in cockerels fed Indoxacarb [77,93,94]. The study concluded that 80% Aqueous acetone extract of Hedychium coronarium flower and other chemical constituents had a hepatoprotective effect, with a significant p < 0.01 value of percentage inhibition [25].…”
Section: Ameliorating Potentialmentioning
confidence: 95%